HOW AI IS INFLUENCING THE ASSESSMENT OF STUDENTS IN PHYSICS (International conference on multidisciplinary science, 2026)
Artificial Intelligence, or AI, is a very popular topic today. Many people think AI is only about robots, but it is actually in our smartphones and computers too. For example, when you use Google Maps or talk to Chatgpt, you are using AI. There are many good things about AI. First, it makes our life easier. It can find information very fast and help us with our homework or work. Second, AI can do boring tasks for us. This gives humans more time to do creative things. However, some people are worried about AI. They think that robots will take our jobs in the future. Also, some students use AI too much and stop thinking for themselves. This is a problem because we need to keep our brains active. In our opinion, AI is a great invention. It is like a powerful tool, such as a car or a computer. If we use it in a smart way, it will help us build a better world. We should not be afraid of it, but we must learn how to use it correctly.